Primary infertility in nuclear industry employees: report from the nuclear industry family study. - Doyle, P; Roman, E; Maconochie, N; Davies, G; Smith, P; Beral, V (2001)
OBJECTIVE: To determine whether men and women who are occupationally exposed to ionising radiation are at increased risk of primary infertility. METHODS: A cross sectional analysis of reproductive outcome was reported in an occupational cohort of nuclear industry workers from the Atomic Energy Authority, Atomic Weapons Establishment, and British Nuclear Fuels in the United Kingdom. Data on employment and radiation monitoring supplied by employers were linked to data obtained from self administered questionnaires sent to all current employees and a sample of past workers. A total of 5353 men and 603 women aged 40 years or more at the time of survey whose first pregnancy, or attempt at pregnancy, had occurred after first employment in the nuclear industry were recruited to the study. Primary infertility was defined as consultation with a doctor about the failure to achieve at least one viable (24 weeks gestational age or more) pregnancy. RESULTS: 2.6% Of men and 3.7% of women reported primary infertility. For men, this proportion did not differ by amount of radiation monitored or by dose received. The prevalence of infertility was higher among monitored women than non-monitored women, but not significantly so and the numbers were too small to draw any firm conclusions. CONCLUSIONS: No support was found for a hypothesis linking exposure to low level ionising radiation among men with primary infertility. There was weak evidence of an association in women, but the relatively few monitored women prevented detailed examination of these data.